Assessing the contributions and quality of various food crops harvested by household on food security in Ugenya Sub-County, Siaya County, Kenya - Odinga, Evans Owen; Mamboleo, Dennis; Nyantika, Dan (Research Journal in Advanced Social Sciences, 2022)
Demand for food and other agricultural products is projected to increase driven by population growth, increasing per capita incomes and changes in diets. Small scale food crop production in Kenya account for about 70 percent of the overall production. The purpose of this study was to investigate the effects of food crop farming on household food security in Ugenya sub-county, Siaya County, Kenya. This study adopted a descriptive research design, a target population of 2608 who include subsistence food crop farmers and experts from department of agriculture from which a sample size of 264 participants was selected. Questionnaires, and interview guide and direct observation were used to collect data. The data obtained from the questionnaire was edited, sorted and coded prior to analysis. The data was keyed into the Statistical Package for Social Sciences (SPSS) for analysis. Frequency and percentages was used to present data that required descriptive statistics. Regression analysis was used to analyze the extent of relationship between variables while data obtained through interviews was presented based on relevant themes. The study findings established that most of the farmers plant various kinds of food crops especially for household consumption this food crops included; maize, beans, sorghum, millet cassavas, potatoes and others.